2023
DOI: 10.1093/jsxmed/qdac051
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy and sexual function: a systematic review and meta-analysis

Abstract: Background Sexual function after hysterectomy can be a concern for patients, and research remains inconclusive about changes in sexual function associated with hysterectomy. Aim We meta-analyzed studies on change in sexual function from pre- to posthysterectomy and the role of total vs subtotal hysterectomy and concomitant bilateral salpingo-oophorectomy (BSO) in differences in such change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The sexually active group were predominantly premenopausal, but we recognize that changes to the menopausal status could represent a possible confounder. A concomitant bilateral salpingo‐oophorectomy in premenopausal women can more severely affect sexual function postoperatively, but in our cohort, this was not a common procedure 8 . Sexual function after hysterectomy is a complicated multifactorial process that depends on various factors, such as body image, emotional factors, the sexual partner as well as communicative matters.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The sexually active group were predominantly premenopausal, but we recognize that changes to the menopausal status could represent a possible confounder. A concomitant bilateral salpingo‐oophorectomy in premenopausal women can more severely affect sexual function postoperatively, but in our cohort, this was not a common procedure 8 . Sexual function after hysterectomy is a complicated multifactorial process that depends on various factors, such as body image, emotional factors, the sexual partner as well as communicative matters.…”
Section: Discussionmentioning
confidence: 73%
“…A concomitant bilateral salpingo‐oophorectomy in premenopausal women can more severely affect sexual function postoperatively, but in our cohort, this was not a common procedure. 8 Sexual function after hysterectomy is a complicated multifactorial process that depends on various factors, such as body image, emotional factors, the sexual partner as well as communicative matters. Hysterectomy results in loss of the uterus, cervix and upper part of the vagina, which may reduce vasocongestion and interrupt the nerve supply resulting in an impairment of sensibility, arousal and the lubrication‐swelling process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovaries are very important for premenopausal and postmenopausal women to produce steroid hormones, which can regulate the central response to sexual stimulation and the sensitivity of genital tissue to tactile stimulation, thus ensuring the comfort of both men and women. 36 It is worth noting that some partners indicated that changes in the patient's body form can also lead to unpleasant sexual experiences. Body image is an important multi-dimensional and complex concept.…”
mentioning
confidence: 99%